Transitivity and Modality in Joe Biden’s Justificatory Speeches about the US Withdrawal from Afghanistan: A Critical Discourse Analysis - Hassan, Ahmed Fleih; Kadhim , Sadiq Mahdi (Journal of Ecohumanism, 2024)
The purpose of this paper is to critically examine transitivity and modality of the US President Joe Biden’s speeches in which he declares the US military’s departure from Afghanistan. The stud tries to answer the following questions: 1.What is the dominant type of transitivity process and modality that is used in Biden’s speech in order to justify his decision to withdraw and justify the American military’s withdrawal? 2.How do transitivity processes and modality reveal the ideological construction in Biden’s speeches to justify the American military’s withdrawal?. The study concluded that the material process the most frequently and dominantly in his speeches, with a percentage of 35% and a frequency of 63 times, while the verbal process is employed the least, with a percentage of 6% and a frequency of 12 times. Modality of prediction is most frequently, 29 times with a percentage of 59%, whereas the modality of possibility and obligation is used twice with a percentage of 4%.It is concluded that material process is used most frequently whereas the verbal process is used least frequently to enforce the idea that action, not words, is what he is known for. It is also concluded that the modality of prediction most frequently to impose the idea that US is comprehending very well the political and military events.